Rare live birth to a 48-year-old woman after embryo transfer with autologous oocyte: A case report - Te-Wei Wu; Horng-Der Tsai; Hsiao-Chin Huang; Hsaio-Hsuan Yang; Yu-Jing Chen; Hsin-Hung Wu; Chen-Hsuan Wu (Elsevier, 2022)
Objective: Advanced maternal age and decreased ovarian reserve have been challenges for assisted reproductive technology (ART). Few cases, using autologous oocytes more than 46-years-old, have previously been reported. We seek to show how the age at which autologous oocytes may successfully be employed may be increasing. Case report: We report a 47-year-old woman with an anti-Müllerian hormone (AMH) level of 0.24 ng/mL, conceived through in vitro fertilization (IVF) using autologous oocytes. Patient was given an antagonist protocol for ovarian stimulation and one frozen-thawed embryo was transferred. The patient became pregnant. The course of her pregnancy was uneventful and she gave birth to a 3330 gm male baby by cesarean section. Conclusion: Technological advances permit women, who previously would have been considered too old to employ an autologous oocyte, to have a successful pregnancy with a live birth.